Effectiveness and mechanisms of the arts therapies in forensic care. A systematic review, narrative synthesis, and meta analysis - Abbing, Annemarie; Haeyen, Suzanne; Nyapati, Sashank; Verboon, Peter; Hooren, Susan van (Frontiers in Psychiatry, 2023)
Mental health care in forensic settings mainly consists of verbal oriented treatments. In addition, experience-based therapies are used, such as (creative) arts therapies: (visual) art therapy, music therapy, drama therapy and dance (movement) therapy. There are indications for effectiveness of arts therapies, but a systematic overview of effect studies of all arts therapies in forensic care is lacking. First, we performed a systematic review. Second, Thematic Analysis was used to synthesize the qualitative narrative results and define the hypothesized mechanisms of change. Third, we performed a meta-analysis to investigate the effects of arts therapies in reducing psychosocial problems of adult patients in forensic (psychiatric) care. Twenty-three studies were included in the review. Quality and risk of bias was assessed using EPHPP (Effective Public Health Practice Project). The included studies were heterogeneous in type of outcome measures and intervention characteristics. Synthesis of mechanisms of change involved in the methodical use of the arts in arts therapies resulted in a description of regulatory processes which are stimulated in arts therapies: perceptive awareness (interoceptive and exteroceptive), the regulation of emotions, stress, impulses, cognitions, social regulation and self-expression. These processes are included in developing prevention, coping and self-management skills. Eighteen studies were included in the meta-analyses (11 RCTs/CCTs; 7 pre-post studies). The meta-analyses indicated significant effects on both risk factors (psychiatric symptoms, addiction) and protective factors for criminal behavior (social functioning, psychological functioning). Effects on criminal and/or antisocial behavior were not significant, but this outcome measure was scarcely used among the studies. The analyses in this study should be considered explorative. More research is needed to gain more solid conclusions about effectiveness and mechanisms of change of arts therapies in forensic care. However, the results of this first systematic review, synthesis of mechanisms and meta-analysis in this field are promising and show effects of arts therapies on risk and protective factors in forensic psychiatric patients.